Exploring Chemical Composition, Antioxidant, Enzyme Inhibitory and Cytotoxic Properties of Glaucium acutidentatum Hausskn. & Bornm. from Turkey Flora: A Novel Source of Bioactive Agents to Design Functional Applications - Yagi, Sakina; Zengin, Gokhan; Uba, Abdullahi Ibrahim; Maciejewska-Turska, Magdalena; Sieniawska, Elwira; Swiatek, Lukasz; Polz-Dacewicz, Malgorzata (Mdpi, 2024)
The present study was performed to determine the chemical constituents, cytotoxicity, antioxidant and enzyme inhibition activities of the aerial parts of Glaucium acutidentatum Hausskn. and Bornm. (family Papaveraceae). Methanolic and aqueous extracts were prepared by maceration, homogenizer-assisted extraction (HAE) and infusion. Results showed that the highest total phenolic and flavonoids contents were obtained from the methanol extracts obtained by HAE (53.22 +/- 0.10 mg GAE/g) and maceration (30.28 +/- 0.51 mg RE/g), respectively. The aporphine, beznyltetrahydroisoquinoline, and protopine types of Glaucium alkaloids have been tentatively identified. Among them, glaucine was identified in all extracts. Flavonoids, phenolic acids, coumarins, organic acids and fatty acids were also detected. Methanolic extract obtained using the HAE method displayed the highest anti-DPPH (41.42 +/- 0.62 mg TE/g), total antioxidant (1.20 +/- 0.17 mmol TE/g), Cu2+ (113.55 +/- 6.44 mg TE/g), and Fe3+ (74.52 +/- 4.74 mg TE/g) reducing properties. The aqueous extracts obtained by infusion and HAE methods exerted the best anti-ABTS (103.59 +/- 1.49 mg TE/g) and chelating (19.81 +/- 0.05 mg EDTAE/g) activities, respectively. Methanolic extract from HAE recorded the highest acetylcholinesterase (2.55 +/- 0.10 mg GALAE/g) and alpha-amylase (0.51 +/- 0.02 mmol ACAE/g) inhibition activities, while that obtained by maceration showed the best butyrylcholinesterase (3.76 +/- 0.31 mg GALAE/g) inhibition activity. Both extracts revealed the best tyrosinase inhibitory activity (25.15 +/- 1.00 and 26.79 +/- 2.36 mg KAE/g, p >= 0.05). G. acutidentatum maceration-derived aqueous extract showed selective anticancer activity against cells originating from human hypopharyngeal carcinoma. In conclusion, these findings indicated that G. acutidentatum is a promising source of alkaloids and phenolic compounds for variable pharmaceutical formulations.
Keywords: Glaucium acutidentatum; alkaloids; phenols; antioxidant; enzyme inhibition; cytotoxicity